Development of tribophysical foundations of lubricity of liquid-crystal additives to base oils - Воронін, Сергій Володимирович (Eastern-European Journal of Enterprise Technologies, 2015)
The model of the tribological system using liquid crystals as anti-friction and anti-wear additives in the base oil was presented in the paper. The model takes into account functional dependences between input and output characteristics of the system through the functional dependence between input characteristics and characteristics of the internal state of the system. Further research in the paper is aimed at establishing the patterns that describe the impact of the internal state of the tribosystem on the main output characteristics - friction force and wear rate under various contact conditions. Dependence for determining the total specific friction force in tribosystems considering the molecular component of the specific friction force in boundary films of liquid crystals and mechanical friction component was given. Dependences for determining the linear wear rate at elastic and elastic-plastic contact in tribosystems were also presented. Such dependences were obtained taking into account the properties of liquid-crystal boundary film. The results of experimental studies of sliding tribosystems on friction machines using liquid crystals as additives to base oils were shown. In studies, the patterns of changes in specific friction force and wear rate in tribosystems depending on the main characteristics of the phase state of liquid-crystal additive were obtained.